2020
DOI: 10.1371/journal.pone.0234150
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the gene expression profiles of rehabilitated Florida manatees (Trichechus manatus latirostris) following red tide exposure

Abstract: To investigate a Florida manatee (Trichechus manatus latirostris) mortality event following a red tide bloom in Southwest Florida, an RNA sequencing experiment was conducted. Gene expression changes in white blood cells were assessed in manatees rescued from a red tide affected area (n = 4) and a control group (n = 7) using RNA sequencing. The genes with the largest fold changes were compared between the two groups to identify molecular pathways related to cellular and disease processes. In total, 591 genes (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Later, a study on white blood cells, collected on manatees rescued from a red tide, confirmed the involvement of the immune response [23]. Using RNA-Seq, Lazensky et al [23] showed that immune response (inflammation, wounds, and injuries), cell proliferation, and apoptosis were the most predominant cellular pathways dysregulated (e.g., OSCAR 12 fold) by red tide. Furthermore, neurodegenerative pathways were particularly affected.…”
Section: Ecotoxicologymentioning
confidence: 98%
See 3 more Smart Citations
“…Later, a study on white blood cells, collected on manatees rescued from a red tide, confirmed the involvement of the immune response [23]. Using RNA-Seq, Lazensky et al [23] showed that immune response (inflammation, wounds, and injuries), cell proliferation, and apoptosis were the most predominant cellular pathways dysregulated (e.g., OSCAR 12 fold) by red tide. Furthermore, neurodegenerative pathways were particularly affected.…”
Section: Ecotoxicologymentioning
confidence: 98%
“…Upregulation of the immune and neurodegenerative pathways. RNA-Seq [23] Tursiops truncatus BTX as haptens that induce an inflammatory immune response.…”
Section: Trichechus Manatus Latirostrismentioning
confidence: 99%
See 2 more Smart Citations
“…Red tide HABs are predominantly composed of the toxic dinoflagellate Karenia brevis, which produces potent natural neurotoxins known as brevetoxins [8]. Red tides occur when environmental conditions favorable to K. brevis cause rapid algal population growth and release brevetoxins into the surrounding environment in high concentrations [9]. K. brevis easily breaks apart in the surf, disperses into marine waters [10], and becomes aerosolized [11].…”
Section: Introductionmentioning
confidence: 99%